KOTA PROBOLINGGO PADA MASA MENJELANG DAN AWAL REVOLUSI - Ari Sapto (Faculty of Humanities, Jember University, 2012)
The revolution era was inseparable from the earlier period. Despite the radical changes during the revolution, the previous elements remained in existene and had significant influences. Probolinggo was a small town, a sea port having agricultural and plantation bases and from the 19th century had an important significance for the Dutch colonial rule, not only in physical but sociocultural es well. Its geographical location near to Madura made it easily accessible for Madurese migration. The Madurese people grew to become the majority and in cultural terms, there was a mix of Madurese and Javanese elements. In the economic sector, the Javanese mostly engaged in wet field agriculture, while the Madurese accuppied a more heterogenous employment. Keywords: population, Probolinggo, revolution, socioeconomy.